PENGARUH PENGELOLAAN PERSEDIAAN TERHADAP PENINGKATAN EFISIENSI PEMBELIAN PADA PT RATU IDAMAN PRATAMA - Zainal Abidin, Alie; Hanafiah, Ali; Syaputra, M. Virgiawan (JOURNAL AKSES STIA MALANG, 2025)
Supermarkets and food retail outlets are essential for contemporary society to meet its demands. To spur competition among business people to expand their operations, businesses are developing from small scale to large scale along with the times. In the supermarket business, implementing good inventory management can have a significant impact on purchasing efficiency. This research aims to examine the effect of inventory management strategies on purchasing efficiency at PT Ratu Idaman Pratama. The population in this study were all employees of PT Ratu Idaman Pratama, while the research sample was 20 people who held staff positions or above. Inventory management is a process of arranging, managing and controlling the amount of goods or materials owned by a company so that they are always available when needed without excesses that can cause additional costs. Meanwhile, purchasing efficiency is the ability to obtain the goods or services needed with good quality and the best price, with minimal time and resources and as economically as possible. Data analysis in this paper uses data quality tests, classical assumption tests, simple linear regression, hypothesis testing, and coefficient of determination. The research results prove that inventory management variables simultaneously have a significant effect on purchasing efficiency. The coefficient of determination value is 0.174. This means that 17.4% of the dependent variable can be explained by the independent variable, namely Inventory Management. It is hoped that from the results of this research, the leadership of PT Ratu Idaman Pratama will always supervise inventory management so that it can increase purchasing efficiency.